TINGKAT PARTISIPASI POLITIK PEMILIH PEMULA PADA PILKADA GUBERNUR 2018 DITINJAU DARI JENIS KELAMIN DAN PENDIDIKAN - Nur Iqrima; Amrazi Zakso; Supriadi Supriadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
The title of this research is “The Level of Politic Participation from the Beginner Voters on the Governor Election 2018 based on the Gender and Education (A Beginner Voters Study at Sambas Sub-District)”. The aims of this research were to find out the level of politic participation from the beginner voters based on their gender, education and also to investigate the factors that influenced the level of the politic participation, especially from the beginner voters based on their gender and education on the Governor Election 2018. This research was conducted through a qualitative approach with a descriptive method. The data for this research were collected by using an interview technique and documentations with the interview guidance and documentation instruments. The result of this research showed that the beginner voters’ gender and education have influenced the level of the politic participation on the Governor Election 2018. In addition, the research also found out three factors that have influenced the level of politic participation from the beginner voters on the Governor Election 2018, which were the social environment factor, the personal factor, the consciousness factor and the credibility factor toward the goverment.